Oxford Scholarship Online 2017
DOI: 10.1093/oso/9780198808039.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Combating Investment Fraud

Abstract: Investment fraud is a significant problem in America. Many Baby Boomers are entering retirement with significant assets, and enforcement actions by financial regulators indicate that investors can be vulnerable to fraud at key ‘wealth events’ in their lives, such as when they face a decision about what to do with money arising from the sale of a house, an inheritance, or an IRA rollover. Protecting these assets—for Baby Boomers and younger generations who face key wealth events—will be important to ensure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Financial literacy and education are often touted as a solution to the problems consumers face, but the findings from this study show that general understanding of financial concepts failed to alleviate experiences of this form of fraud or mistreatment. In fact, those who are more financially knowledgeable had a higher probability of having their financial accounts compromised, which is consistent with previous studies finding the positive association between financial literacy and investment fraud victimization (AARP, 2007 ; Kieffer & Mottola, 2017 ). However, the fact that financial skill shows a consistent relationship with positive outcomes (being less likely to be mistreated and defrauded) provides insights to what an effective intervention looks like.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Financial literacy and education are often touted as a solution to the problems consumers face, but the findings from this study show that general understanding of financial concepts failed to alleviate experiences of this form of fraud or mistreatment. In fact, those who are more financially knowledgeable had a higher probability of having their financial accounts compromised, which is consistent with previous studies finding the positive association between financial literacy and investment fraud victimization (AARP, 2007 ; Kieffer & Mottola, 2017 ). However, the fact that financial skill shows a consistent relationship with positive outcomes (being less likely to be mistreated and defrauded) provides insights to what an effective intervention looks like.…”
Section: Discussionsupporting
confidence: 90%
“…Deliema et al ( 2019 ) found that those who were isolated from others and did not have anyone to discuss a scam offer, those who were financially insecure, and those with less financial knowledge were more likely to be victims of financial scams. However, other studies on investment-specific fraud found the opposite—that higher financial literacy is associated with higher rates of fraud victimization (AARP, 2007 ; Kieffer & Mottola, 2017 ). Fraud is a complex topic, and the individuals who are targeted differ based on the type of fraud.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In our case, resources and financial competence among older adults with advantaged socioeconomic conditions may enable them to engage more in financial matters. They may also hold relatively open attitudes toward financial matters and risks, as found in previous scholarship (e.g., Awais et al, 2016;Kieffer & Mottola, 2017). Consequently, these older adults may have a higher likelihood to become victims because they have more exposure to fraudsters and possibly are more likely to make transactions and take risks related to fraudsters' requests due to their relatively open financial attitudes.…”
Section: Theoretical Considerationsmentioning
confidence: 69%
“…They may also tend to make transactions without prudent consideration, given their great willingness to engage in financial matters (Hindelang et al, 1978). Kieffer and Mottola's (2017) findings on the positive association of open financial attitudes with impulsive consumption could buttress this explanation. Our findings suggest that professionals in gerontology and finance should pay attention to older clients who have relatively advantaged socioeconomic conditions and strong interest in financial matters, given their heightened risk of financial exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…Other costs include legal fees, late fees, and lost wages, and are often not taken into account. Nor are non-financial costs of fraud such as stress and depression (Kieffer & Mottola, 2016).…”
Section: Fraudulent Investment Productsmentioning
confidence: 99%